A New Routing Protocol for Efficient and Secure Wireless Sensor Networks - Zhang Yu-quan; Wei Lei (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
This paper presents an improved LEACH protocol to save energy and enhance network security for wireless sensor networks. All nodes are distributed evenly in sensing area. The sensing area is divided into a number of small squares called cells, and a cluster consists of four cells. The cluster structure does not change in whole network lifetime. A cell head is chosen in each cell and a cluster head is selected from four cell heads in each cluster. The data are transmitted from clusters to the base station by employing the multi-hop manner. All nodes that communicate each other establish pairwise keys. Analysis demonstrates that the new routing protocol saves more node energy, distributes energy consumption to all nodes more evenly, prolongs more lifetime for WSNs than the LEACH protocol dose. Moreover, it enhances the security for WSNs. DOI: http://dx.doi.org/10.11591/telkomnika.v11i11.3530